2018
DOI: 10.1111/pde.13382
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric psoriasis: Evolving perspectives

Abstract: Pediatric psoriasis is an important immune-mediated inflammatory skin disease with potential for significant impact on affected individuals and their caregivers. Current state-of-the-art care is based primarily on experience and expert consensus, but pediatric data are accumulating and therapeutic options are rapidly evolving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 89 publications
1
60
0
5
Order By: Relevance
“…Despite the availability of new drugs in children as well, there is still a scarce number of randomized controlled trials evaluating therapies of moderate-to-severe psoriasis in children and adolescents. Therefore standardized management guidelines are lacking (Eichenfield et al, 2018). Long-term analysis in childhood are available for open-label etanercept, ustekinumab versus placebo (Landells et al, 2015;Paller et al, 2016), and more recently for adalimumab as well (Thaci et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of new drugs in children as well, there is still a scarce number of randomized controlled trials evaluating therapies of moderate-to-severe psoriasis in children and adolescents. Therefore standardized management guidelines are lacking (Eichenfield et al, 2018). Long-term analysis in childhood are available for open-label etanercept, ustekinumab versus placebo (Landells et al, 2015;Paller et al, 2016), and more recently for adalimumab as well (Thaci et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…P soriasis develops during childhood in almost onethird of cases, with an almost linear increase in prevalence rates until 18 years of age (1)(2)(3)(4)(5). Nail psoriasis affects over 50% of the adult population with psoriasis, and is even more prevalent in patients with psoriatic arthritis (PsA) (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Approximately one-third of children with psoriasis experience more severe or recalcitrant disease (5,22). Early identification of children with an increased risk for a severe disease course is essential for adequate intervention and subsequent limitation of disease progression.…”
mentioning
confidence: 99%
“…Studies on scalp psoriasis in children and potential associations with clinical characteristics are sparse. In children, the scalp is commonly reported as the initial site of presentation and scalp psoriasis tends to develop more frequently in girls than in boys . One multicentre study reported scalp psoriasis more frequently in severe vs. moderate psoriasis but the finding did not reach statistical significance .…”
Section: Comparison Of Clinical Characteristics Between Children Withmentioning
confidence: 99%